IMPLEMENTASI KONSEP EMOTIONAL SPIRITUAL QUOTIENT (ESQ) LEARNING TERHADAP KARAKTER RELIGIUS SISWA KELAS V MI NW SEGAET - Bisyrulhafy; Bq. Indana Zulfa; Helmi Kuriani (Al-mujahidah, 2021)
Character is a reflection of a person's self. In forming character, it is necessary to apply good values, especially to the religious character of MI students. Some students have bad behavior The behavior that the researcher meant was: there are still students who call their teachers loudly and also dishonest with their teachers such as permission to go to the bathroom during class hours but do not come back after recess and then return to class so it cannot be said to be commendable behavior because it is important to instill good values to shape the religious character of students, especially in MI students where their thinking is still labile and quickly accepts the changes of this era. This study aims to determine how the implementation of the Emotional Spiritual Quotient (ESQ) concept on the religious character of class V MI NW students segaet. This research is a descriptive qualitative research, data collection is carried out by observation, interviews and documentation. The result of this study is that the concept of Emotional Spiritual Quotient (ESQ) learning on the religious character of grade V students is relevant to character education in class V MI NW segaet, it is shown that there are 6 pillars of Faith, 5 pillars of Islam. In the Emotional Spiritual Quostient (ESQ) concept, principles taken from the pillars of faith and pillars of Islam are taught, as for the implementation of the Emotional Spiritual Quotient (ESQ) learning concept on the religious character of grade V students, there are several ways of applying the Emotional Spiritual Quotient (ESQ) concept such as getting used to saying greetings to anyone, especially when entering class and getting used to praying before starting learning and before going home from school and being taught to always respect obeying parents and teachers, Always do good to everyone, care for others and the environment and are taught to be polite.